(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effect of using Viggo-Tuski’s theory on the achievement of fifth grade female students in the subject of Biology)In order to confirm the aim of the research, the researcher put the following main null hypothesis:- There is no statistically significant difference at the significance level (0.05) between the average scores of the students of the experimental group who studied according to Vygotsky’s theory and the average scores of the students of the control group who studied according to the usual method in the achievement test.